TRANSLATOR SKILL METHODS - Kiyаsоvа, Rа’nо (Журнал иностранных языков и лингвистики, 2023)
Sometimes our students say, is translation a literary phenomenon or is scientific thinking a product? they appeal with the question. In this question, one can observe the embodiment of not superficial interest, but the desire to understand the essence of the problem and reach its root. Indeed, an interesting question. In the explanatory dictionary of the Uzbek language, it is described as a translation of a text that is rolled from one language to another, while in Wikipedia it is interpreted as a translation, the rendering of a text in one language in another, which is the main manifestation of interethnic communication.